Expression of Two Foreign Genes by a Newcastle Disease Virus Vector From the Optimal Insertion Sites through a Combination of the ITU and IRES-Dependent Expression Approaches - He, Lei; Zhang, Zhenyu; Yu, Qingzhong (Frontiers in Microbiology, 2020)
Many Newcastle disease virus (NDV) strains have been developed as vectors to express a foreign gene (FG) for vaccine and cancer therapy purposes. The non-coding region between the phosphoprotein (P) and matrix protein (M) genes and the non-coding region behind the NP gene open reading frame (ORF) in the NDV genome have been identified as the optimal insertion sites for efficient FG expression through the independent transcription unit (ITU) and the internal ribosomal entry site (IRES) dependent expression approaches, respectively. To date, however, the majority of these NDV vectors express only a single or two FGs from suboptimal insertion sites in the NDV genome, obtaining various levels of FG expression. To improve the FG expression, we generated NDV LaSota vaccine strain-based recombinant viruses expressing two FGs, GFP, and RFP, from the identified optimal insertion sites through a combination of the ITU and IRES-dependent approaches. Biological assessments of the recombinant viruses indicated that the recombinants expressing two FGs were slightly attenuated with approximately one order of magnitude lower in virus titers when compared to the viruses containing a single FG. The FG expression efficiencies from the two-FG viruses were also lower than those from the single-FG viruses. However, the expression of two FGs from the optimal insertion sites was significantly (p < 0.05) higher than those from the suboptimal insertion sites. The expressions of FGs as monocistronic ITU were approximately 4-fold more efficient than those expressed by the bicistronic IRES-dependent approach. These results suggest that the NDV LaSota vector could efficiently express two FGs from the identified optimal insertions sites. The ITU strategy could be used for “vectoring” FGs in circumstances where high expression of gene products (e.g., antigens) is warranted, whereas, the IRES-dependent tactic might be useful when lower amounts of IRES-directed FG products are needed.